2022
DOI: 10.3389/fendo.2022.1015319
|View full text |Cite|
|
Sign up to set email alerts
|

Lobectomy may be more appropriate for patients with early-stage medullary thyroid cancer older than 60 years old

Abstract: PurposeClinical guidelines presently recommend total thyroidectomy for the treatment of medullary thyroid cancer (MTC). This study was aimed to investigate whether lobectomy could be the initial treatment for stage I MTC patients.MethodsThe retrospective study was based on data from the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and 2015. The risk factors of survival were estimated by the univariate and multivariate Cox proportional-hazards model. The effect of age on death risk w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…An international, multicenter series from 1983 to 2011 of 313 patients with sporadic MTC showed a 5.6% rate of bilateral foci 12 on final pathology but did not examine whether those were detectable tomy with ipsilateral central neck dissection. 13,14 The safety of this approach in select patients with MTC has already been shown in previous studies, 7,10 although they did not quantify the risk of undetected foci of MTC in the contralateral lobe. Many thyroid specialists may also recommend total thyroidectomy not to remove occult contralateral foci, but rather to facilitate surveillance with serum calcitonin.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…An international, multicenter series from 1983 to 2011 of 313 patients with sporadic MTC showed a 5.6% rate of bilateral foci 12 on final pathology but did not examine whether those were detectable tomy with ipsilateral central neck dissection. 13,14 The safety of this approach in select patients with MTC has already been shown in previous studies, 7,10 although they did not quantify the risk of undetected foci of MTC in the contralateral lobe. Many thyroid specialists may also recommend total thyroidectomy not to remove occult contralateral foci, but rather to facilitate surveillance with serum calcitonin.…”
Section: Discussionmentioning
confidence: 96%
“…The low rate of contralateral foci should allow select patients to undergo a staged approach to surgery, beginning with initial thyroid lobectomy with ipsilateral central neck dissection . The safety of this approach in select patients with MTC has already been shown in previous studies, although they did not quantify the risk of undetected foci of MTC in the contralateral lobe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found no incidence of contralateral disease. Yang et al reported lobectomy as an appropriate treatment for those older than 60 years. Essig et al reported multifocality in sporadic medullary carcinoma in their multicenter international study.…”
mentioning
confidence: 99%